2022
DOI: 10.3390/medicina58030365
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Tumour Microenvironment Components in Malignant Melanoma

Abstract: Malignant melanoma has shown an increasing incidence during the last two decades, exhibiting a large spectrum of locations and clinicopathological characteristics. Although current histopathological, biochemical, immunohistochemical, and molecular methods provide a deep insight into its biological behaviour and outcome, melanoma is still an unpredictable disease, with poor outcome. This review of the literature is aimed at updating the knowledge regarding melanoma’s clinicopathological and molecular hallmarks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 303 publications
(465 reference statements)
1
6
0
Order By: Relevance
“…The lesions included in our study group showed the presence of BRAF mutations in 57.69% of cases diagnosed with primary MMs, in agreement with percentages reported in other studies [ 1 , 26 , 27 ]. On the other hand, the mutated BRAF genotype was identified in only 38.18% of cases of metastatic MMs.…”
Section: Discussionsupporting
confidence: 92%
“…The lesions included in our study group showed the presence of BRAF mutations in 57.69% of cases diagnosed with primary MMs, in agreement with percentages reported in other studies [ 1 , 26 , 27 ]. On the other hand, the mutated BRAF genotype was identified in only 38.18% of cases of metastatic MMs.…”
Section: Discussionsupporting
confidence: 92%
“…The emergence of 3D in vitro models contributed to the development of more advanced and physiologically relevant systems for cancer study [ 42 ], including UM. One factor that influences melanoma behavior in the tumor microenvironment (TME), especially its cellular components which might contribute to cancer progression and resistance to therapy [ 46 ]. Particular attention was given to the influence of TME on UM behavior using established 3D models.…”
Section: Current Status Of Rare Melanoma Experimental Modelsmentioning
confidence: 99%
“…Malignant melanoma accounted for ~3% of all tumors in the United States in 1998 (1) and may be caused by the malignant transformation of dysplastic nevi, junctional nevi and benign melanocytic nevi (2,3). Based on their location, malignant melanomas are generally classified into cutaneous malignant melanomas (skin and acra; 90%), mucosal malignant melanomas (mucosa of head, neck, gastrointestinal, conjunctiva and genital areas; 8-15%), uveal malignant melanomas (uvea and ciliary body; 3-5%) and central nervous system (CNS) malignant melanomas (dopaminergic neurons in the substantia nigra and locus coeruleus; 1%) (4)(5)(6). Although CNS melanomas are rare, primary malignant melanomas in the spinal canal are even more rare, with only a few cases reported thus far (7,8).…”
Section: Introductionmentioning
confidence: 99%